Cyber security standards, practices and industrial applications : systems and methodologies - Zubairi, Junaid Ahmed, 1961-; Mahboob, Athar, 1971- (Hershey, PA : Information Science Reference, 2012)
"This book details the latest and most important advances in security standards, introducing the differences between information security (covers the understanding of security requirements, classification of threats, attacks and information protection systems and methodologies) and network security (includes both security protocols as well as systems which create a security perimeter around networks for intrusion detection and avoidance)"--Provided by publisher.
"Premier reference source"--P. [1] of cover.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Computer networks -- Security measures; Computer security; Data protection; Electronic data processing departments -- Security measures